2020
DOI: 10.1111/nph.16607
|View full text |Cite
|
Sign up to set email alerts
|

Life in the canopy: community trait assessments reveal substantial functional diversity among fern epiphytes

Abstract: Summary The expansion of angiosperm‐dominated forests in the Cretaceous and early Cenozoic had a profound effect on terrestrial biota by creating novel ecological niches. The majority of modern fern lineages are hypothesized to have arisen in response to this expansion, particularly fern epiphytes that radiated into the canopy. Recent evidence, however, suggests that epiphytism does not correlate with increased diversification rates in ferns, calling into question the role of the canopy habitat in fern evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 96 publications
2
30
0
Order By: Relevance
“…Lower water availability in the canopy habitat likely selected for reduced xylem tissues to prevent embolism, as well as fewer stomata to lower leaf water loss. As ferns rely entirely on primary xylem due to lack of secondary growth and limited leaf venation to supply lamina tissues, reductions in xylem area could constrain frond morphology and leaf hydraulic function (Brodribb, Feild, & Jordan, 2007;Nitta et al, 2020;Pittermann, Brodersen, & Watkins, 2013;Pittermann et al, 2011Pittermann et al, , 2015. Shorter stipes, however, appear to compensate for selection of reduced xylem tissue by decreasing hydraulic path length.…”
Section: Anatomical and Biomechanical Traits Regulate How Epiphytic Ferns Thrive In Sub-optimal Resource Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower water availability in the canopy habitat likely selected for reduced xylem tissues to prevent embolism, as well as fewer stomata to lower leaf water loss. As ferns rely entirely on primary xylem due to lack of secondary growth and limited leaf venation to supply lamina tissues, reductions in xylem area could constrain frond morphology and leaf hydraulic function (Brodribb, Feild, & Jordan, 2007;Nitta et al, 2020;Pittermann, Brodersen, & Watkins, 2013;Pittermann et al, 2011Pittermann et al, , 2015. Shorter stipes, however, appear to compensate for selection of reduced xylem tissue by decreasing hydraulic path length.…”
Section: Anatomical and Biomechanical Traits Regulate How Epiphytic Ferns Thrive In Sub-optimal Resource Environmentsmentioning
confidence: 99%
“…Therefore, evolutionary selection for physiological and anatomical traits to adapt to these variable environmental conditions should have coincided with the opportunistic diversification of ferns into new epiphytic niches. Indeed, Nitta, Watkins, and Davis (2020) found that, at the community level, epiphytic species were significantly more diverse functionally than terrestrial taxa.…”
mentioning
confidence: 99%
“…We used microclimate data collected by Nitta et al (2020). This dataset includes relative humidity (RH) and temperature measured every 15 min from 2013-07-07 to 2014-07-05 at the fern survey sites with Hobo ProV2 dataloggers (Onset Computer Corporation, Bourne, Massachusetts, USA), and vapor pressure deficit (VPD) calculated from these two values.…”
Section: Microclimatementioning
confidence: 99%
“…Anatomical and physiological traits described by the leaf economic spectrum are often studied in plants (Bruelheide et al, 2018), although difficult to sample in largescale studies. Among ferns, morphological traits such as lifeform and plant size are widely used for describing functional diversity (Kluge and Kessler, 2007;Tanaka and Sato, 2015;Carvajal-Hernández et al, 2018;Nitta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on fern functional diversity along elevational gradients found that morphological trait diversity mirrors species richness patterns. In Costa Rica and Mexico, species richness and trait diversity show a hump-shaped pattern with maximum values at mid-elevation, Japan a monotonic decline, and the island of Moorea in French Polynesia a linear increase for epiphytes (Kluge and Kessler, 2007;Tanaka and Sato, 2015;Carvajal-Hernández et al, 2018;Nitta et al, 2020). Using a null model to exclude the influence of species richness, Kluge and Kessler (2007) found that for epiphytic ferns in Costa Rica, mid-elevations had higher than expected trait diversity, whereas upper and lower elevations maintained lower diversity.…”
Section: Introductionmentioning
confidence: 99%